2020
DOI: 10.1142/j_10.36924sbe.2020.3104
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Extrinsic and Intrinsic Rewards on Employee Retention among Gen Y: A Study in Malaysian Manufacturing Companies

Abstract: The aim of this study is to investigate the relationship between extrinsic and intrinsic reward on retention among Gen Y employees in Malaysian manufacturing companies. The data was collected from 113 respondents worked in manufacturing companies located in Seri Kembangan, Selangor using questionnaires. Multiple regression analysis was conducted to test the hypotheses. The results showed both extrinsic and intrinsic reward are the factors influencing retaining Gen Y in manufacturing companies. The discussion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
5
0
3
Order By: Relevance
“…This sheds light on the significance of cultivating an environment that nurtures intrinsic motivation to enhance employee retention rates, thereby potentially contributing to the overall success and stability of telecommunication firms operating in Pakistan. Similarly, the findings of the study by Hassan and Govindhasamy (2020) revealed that intrinsic rewards (autonomy, orientation of workplace, competence and relatedness) significantly enhanced employee retention in Malaysian manufacturing companies. This study underscores the importance of intrinsic motivational factors in retaining employees, suggesting that when employees feel empowered, valued, and connected within their workplace, they are more likely to remain committed to their organization.…”
Section: Empirical Review Of Self-determination Factors and Retention...mentioning
confidence: 60%
“…This sheds light on the significance of cultivating an environment that nurtures intrinsic motivation to enhance employee retention rates, thereby potentially contributing to the overall success and stability of telecommunication firms operating in Pakistan. Similarly, the findings of the study by Hassan and Govindhasamy (2020) revealed that intrinsic rewards (autonomy, orientation of workplace, competence and relatedness) significantly enhanced employee retention in Malaysian manufacturing companies. This study underscores the importance of intrinsic motivational factors in retaining employees, suggesting that when employees feel empowered, valued, and connected within their workplace, they are more likely to remain committed to their organization.…”
Section: Empirical Review Of Self-determination Factors and Retention...mentioning
confidence: 60%
“…Gambar 1. Model Penelitian Sumber : Modifikasi model dari (Sepahvand & Khodashahri, 2021), (Xuecheng et al, 2022), dan (Hassan & Govindhasamy, 2020).…”
Section: Model Penelitianunclassified
“…Kemudian hasil penelitian ini menunjukkan bahwa penghargaan dapat meningkatkan motivasi karyawan sehingga meningkatnya juga keterlibatan karyawan terhadap restoran tersebut. Penelitian ini berjalan sesuai dengan penelitian terdahulu yang dibuat oleh (Alhmoud & Rjoub, 2020;Mellyana et al, 2021;Hassan & Govindhasamy, 2020;Amadi et al, 2021). (Geh Ming et al, 2021;Ramalu & Kalimuthu, 2022).…”
Section: Reward Berpengaruh Positif Terhadap Employee Engagementunclassified
See 1 more Smart Citation
“…Y Generation has its characteristics in its demand for appreciation and support from the company, one of the supports that Y Generation employees want is rewards. (Hassan and Govindhasamy, 2020). Ali, Amin, and Hamid (2016) argue that there are two types of rewards, extrinsic rewards, and intrinsic rewards.…”
Section: Volume 3 Number 1 2023mentioning
confidence: 99%